Gender equality and sustainable development in Nigeria: Issues and challenges - Dupe Adesubomi Abolade (Trends Economics and Management, 2021)
Purpose of the article: The objective of this study was to examine issues and challenges of gender equality in Nigeria in relation to the achievement of the desired sustainable development in the nation. Methodology: The study adopted survey research design. One hundred and sixty females were randomly selected from the State Secretariat, Ibadan as a sample population for the study. A set of self-structured questionnaire which had four sections were used as instrument for data collection. One hundred and forty properly filled questionnaire were analysed. Three hypotheses were generated and tested. Scientific aim: The study examined these three factors: socio-cultural factors, workplace discrimination and women participation in political activities in Nigeria to find out if there is equality between male and female genders in Nigeria that could translate to sustainable development in the nation. Findings: The study establishes that there is no equality between the genders; that women are discriminated against and they still play the second fiddle and that the inequality hinders the coveted sustainable development in the nation. Conclusion: It therefore recommends that the government and its agencies and employers of the workforce have the political will to include the female gender in the scheme of things and put them on the same level as their male counterparts for the achievement of development in the nation that will indeed be sustainable.
Keywords: D63; J31; J71; Q01; 650; gender equality; sustainable development; patriarchal society; socio-cultural factors; illiteracy